1975
DOI: 10.1007/bf01070885
|View full text |Cite
|
Sign up to set email alerts
|

The effect of manometric assembly diameter on intraluminal esophageal pressure recording

Abstract: Recent studies indicate that lower esophageal sphincter pressure is influenced by manometric assembly diameter. This study determines the effect of assembly diameter on both esophageal sphincter pressure and peristaltic pressure in the esophageal body. We performed esophageal manometric studies in 6 normal subjects using graded assembly diameters. High-fidelity recording was achieved by using a noncompliant catheter-infusion system. The results indicate that increases in assembly diameter cause significant inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1
1

Year Published

1976
1976
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 9 publications
5
23
1
1
Order By: Relevance
“…Catheter diameter is another important variable in the consideration of reported values for pressure measurements. Earlier studies have shown that catheters of different diameters will measure different pressures [13,14]. These findings have been confirmed by Wilson et al [4] although the catheters they used were not only of differing diameters but also of different types.…”
Section: Asymmetrysupporting
confidence: 63%
“…Catheter diameter is another important variable in the consideration of reported values for pressure measurements. Earlier studies have shown that catheters of different diameters will measure different pressures [13,14]. These findings have been confirmed by Wilson et al [4] although the catheters they used were not only of differing diameters but also of different types.…”
Section: Asymmetrysupporting
confidence: 63%
“…The effective diameter, Do~, is related to D (the diameter of a tube without a pharynx, for example, a question might be raised about the effect of a tube on the effectiveness of a stripping wave in clearing the pharyngeal lumen. In the esophagus, the contractile characteristics are reported to be affected by distention of the esophageal lumen by the manometric probe previous to neurologic stimulation of muscle contraction [12,13]. Specifically, the larger the catheter diameter, the higher the pressure amplitude from within the closed segment.…”
Section: What Does a Manometermentioning
confidence: 99%
“…Although circumferential sensors alleviate the issue of radial pressure asymmetry, the increased diameter required to accommodate the sensors may counteract this advantage when looking at pressures in the pharynx. Variation in manometric recordings has been confirmed in relation to an increase in catheter diameter [23], as well as in response to stress [24], which could arguably play a role in the tolerance of a larger catheter. In addition, bolus flow is influenced by catheter diameter [17], suggesting that a smaller-diameter catheter may provide more representative pharyngeal pressures related to swallowing.…”
Section: Discussionmentioning
confidence: 93%